P013 Driving improvement through audit: impact of 2017 regional audit and survey upon giant cell arteritis services in 2020. (26th April 2021) - Sharp, Charlotte A; Little, Jayne; Shahbaz, Aqsam; Wood, E F; Wig, Surabhi; Watson, Pippa; Varughese, Sneha; Teh, Lee-Suan; Shah, Preeti; Saleh, Christopher; Ottewell, Lesley; Newton, Laura; et al.
Abstract: Background/Aims In 2017 an audit and survey of giant-cell arteritis (GCA) services were conducted across northwest England (reported previously). This re-survey in 2020, following publication of revised BSR guidance, sought to identify what changes were made in the intervening period, and provided the opportunity to assess the impact of COVID-19. Methods Rheumatologists from 16 hospitals in northwest England were invited to complete a survey in July 2020. Questions focused on service provision for GCA, including pathways, diagnostics and steroid prescription. Results Responses were received from 14/16 sites in 2017, and 15/16 in 2020. 9/15 (60%) sites reported that the 2017 audit and survey prompted changes to GCA services, with two (13%) stating that it clarified the need for implementation of existing plans. Two sites had a GCA pathway in 2017. Four of the seven sites who committed to introducing one have now done so, bringing the total in 2020 to six. Eight of the nine remaining sites plan to implement one, six with a specific date within six months. Six (40%) have completed additional local audit/QI since 2017. Temporal artery (TA) ultrasound (US) is now available in an additional four sites, bringing the total to 6/15 (40%) in 2020. Two sites reported improvement in both time between first rheumatology consultation and TA biopsy, and time to receive results (now <7 days for each task in 6/15 (40%)). Six additional sites reported providing leaflets on steroids routinely, bringing the total in 2020 to 12/15 (80%), versus 6/14 (43%) previously. Four sites (27%) now have a database of GCA patients (one in 2017). There was no major change in sites having a standard protocol for steroid taper (n = 8 2017; n = 7 2020, 89% and 100% of whom respectively use BSR guidance), nor in the number of patients routinely provided steroid cards (six in 2017; five in 2020). The three sites who do not report giving leaflets on steroids routinely, all had a pathway. 8/15 (53%) reported COVID-19 having an adverse effect upon services, including: reduced access to diagnostics (n = 7: TA US, biopsy, and PET-CT); delayed appointments (n = 4); delayed referrals (n = 3). The tertiary referral centre reported an improvement because access to tocilizumab was facilitated by a relaxation of rules by NHS England. Conclusion The original audit and survey of current GCA practice in 2017 highlighted areas for improvement for each site, and regionally. Sites contributing to this re-survey report that the exercise stimulated them to improve their current care. The 2017 exercise showed a strong correlation between reported practice (survey) and actual practice (audit), leading us to have confidence that responses provided a true picture of care. This work demonstrates the power of audit to drive improvement, at a regional level. Disclosure C.A. Sharp: None. J. Little: None. A. Shahbaz: None. E.F. Wood: None. S. Wig: None. P. Watson: None. S. Varughese: None. L. Teh: None. P. Shah: None. C. Saleh: None. L. Ottewell: None. L. Newton: None. S.R. Moore: None. E. McCarthy: Consultancies; E.M. has received consultancy fees from Chugai. E. MacPhie: None. K. Lazarewicz: None. J. Brockbank: None. J. Bluett: None. L. Mercer: None.